Seaweed blooms in paradise: Ecological reflexivity, governance and the Sargassum crisis in the Mexican Caribbean (Ocean and Coastal Research, 2024)
Seaweed blooms pose a compelling governance challenge caused by the new environments of the Anthropocene. Along the Quintana Roo coastline, nestled in the heart of the Caribbean, the onset of extensive Sargassum infestations began in late 2014, posing a formidable environmental management dilemma for state and federal authorities. This study describes the institutional responses elicited by the Sargassum influx on Mexico’s Caribbean shoreline, particularly focusing on Cancún and the Riviera Maya. It proposes ecological reflexivity as a promising governance principle for institutions faced with increasingly complex and unforeseeable circumstances, such as the massive arrivals of Sargassum. Based on a comprehensive analysis of national press reports, active participation in forums and seminars, and in-depth interviews, our research identifies three distinct governance phases. We explore these phases considering the concept of ecological reflexivity. Our findings make a strong case for acknowledging institutional errors and shortcomings as an indispensable aspect of formulating effective strategies to combat unexpected and unfamiliar phenomena such as seaweed blooms. Moreover, governance strategies for dealing with Sargassum in Quintana Roo should not only consider responding to human interests and sustaining the tourist industry. Instead, they should encompass an approach that considers the interplay between human and non-human components within the socio-ecological system.